Visual Storytelling for Knowledge Translation: A Study on BRAC’s Novel Health Loans in Protecting the Poor Against Health and Asset Vulnerability In Bangladesh - Rahman, Mahima; Tamjid, Rafee; Islam, Muhammed Nazmul; Rahman, Mushfiqur; Rabbani, Atonu; Sarker, Malabika (Frontiers in Tropical Diseases, 2021)
Knowledge Translation (KT) is a dynamic and iterative process that includes synthesizing, disseminating, exchanging, and ethically sound application of knowledge to improve health and strengthen the health care system. It facilitates sharing the information generated through research outcomes with the public, the policymakers, or others for further scaling up or continuation of the interventions. Literature suggests a substantial gap exists in communicating with the decision-makers. BRAC JPGSPH produced a documentary/video that iterates how BRAC’s revised medical treatment loan program (MTL+) works with its microcredit clients and modalities. After reviewing all possible options for communication, the video was chosen as the best knowledge translation tool. The video creation and dissemination process are comprised of four phases: pre-production, production, post-production, and exhibition. The video production team reviewed documents and articles and conducted multiple interviews before developing the script. Later, a series of interviews were taken with the beneficiaries who receive medical treatment loans, mid-level, senior managers at BRAC, and researchers. After the production, the director, with a professional editor, edited the video. Over three hours of footage was viewed and ultimately compiled into a six-minute-long video documentary. The audience for the video was more expansive than narrow; from potential beneficiaries to policymakers and every group of stakeholders in between, the video was well-understood. The new MTL+ was integrated into the main program and would be scaled up soon.